Blockade of Erythropoietin-Producing Human Hepatocellular Carcinoma Receptor B1 in Spinal Dorsal Horn Alleviates Visceral Pain in Rats - Chen-Li Sun; Cheng-Wen Li; Nong He; Yuan-Zhang Tang; Xiu-Liang Li; Fu-Shan Xue; Jia-Xiang Ni (Pain Research and Management)
Objective. This experiment was designed to determine whether erythropoietin-producing human hepatocellular carcinoma (Eph) receptors were involved in the development of visceral pain. Methods. Adult male Sprague-Dawley rats were randomly divided into three groups receiving different treatments (n = 16 per group): intracolonic vehicle (control group), intracolonic 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) (TNBS group), and intracolonic TNBS and intrathecal EphB1 receptor blocking reagent (TNBS + EphB2-Fc group). Visceral hyperalgesia was evaluated with quantification of visceral pain threshold induced by colorectal distention. The spinal expressions of EphB1 and ephrinB2 and levels of their phosphorylated forms (p-EphB1 and p-ephrinB2) were assessed by Western blotting and immunohistochemistry. Results. The TNBS-treated rats developed significant visceral hyperalgesia. The spinal expressions of EphB1, p-EphB1, ephrinB2, and p-ephrinB2 were significantly increased in the TNBS group compared with the control group, but visceral hyperalgesia and elevation of spinal EphB1 and p-EphB1 expressions were evidently alleviated by intrathecal administration of EphB2-Fc in the TNBS + EphB2-Fc group. The number of EphB1- and p-EphB1-immunopositive cells, the average optical (AO) value of EphB1, and its phosphorylated form in the spinal dorsal horn were significantly increased in the TNBS group than in the control group, but they were obviously reduced by intrathecal administration of EphB2-Fc. There were no significant differences in the number of ephrinB2- and p-ephrinB2-immunopositive cells and the AO value of ephrinB2 and its phosphorylated form between the TNBS and TNBS + EphB2-Fc groups. Conclusion. EphB1 receptors in the spinal dorsal horn play a pivotal role in the development of visceral pain and may be considered as a potential target for the treatment of visceral pain.